The Reliability Test Of Indonesian Wearing-Off Questionnaire-19 (WOQ-19) - Aji, Jovan; Rizaldy Taslim, Pinzon (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Introduction : Wearing-off is a common complication that happen on Parkinson’s patient with dopaminergic therapy. Identifying when wearing-off occurs is important because it can help medication and increase patient’s quality of life. One of the instruments that can be used to help identifying wearing-off phenomenon is the Wearing-off Questionnaire-19 (WOQ-19). However, there is no translated version of Indonesian WOQ-19 that has been tested for it’s reliability. Objective : To measure the reliability of Indonesian Wearing-off Questionnaire-19 as an instrument to identify wearing-off phenomenon on Parkinson patient. Material and methods : The original version of Wearing-off Questionnaire-19 translated to Indonesian language with forward-backward translation procedure and approved by the original author. This is an observational; cross sectional study carried out at Yogyakarta Bethesda Hospital. Thirty Parkinson’s patients from October to December 2023 in medical records and the result of WOQ-19 Indonesian version. The reliability of the questionnaire were measured by Cronbach α and intraclass correlation coefficient. Result and Discussion : Study conducted on 30 Parkinson’s patients with mean age 70.73 ± 8.68 dominated by men 66.6% and mean duration of Parkinson’s disease 5.2 years. The Indonesian WOQ-19 showed good reliability with intraclass correlation coefficient of 0.796 (IC 95%) and good internal consistency with Cronbach alpha of 0.683. Conclusion : Indonesian WOQ-19 is reliable as an instrument that can be used to detect wearing-off phenomenon on Parkinson’s patients.